Personality Development during Teacher Preparation - Corcoran, Roisin P.; O’Flaherty, Joanne (Frontiers in Psychology, 2016)
Objective: The purpose of this three-year longitudinal study was to examine student teachers’ trajectories of personality as measured by the IPIP Big-Five factor markers and to what extent are there intra-individual and inter-individual changes in personality during this developmental period. The relationship between students’ personality traits, social desirability and prior academic attainment was also examined. Method: This three-year longitudinal study invited participants from the first year of a four-year undergraduate (UG) pre-service teacher education program, the class of 2017. The sample consisted of 305 students. Results: The results suggest that extraversion, agreeableness, conscientiousness, emotional stability, and openness to experience were best represented by a non-significant longitudinal change in means. Results also suggest that social desirability predict agreeableness, and emotional stability, with small to moderate effect sizes. Conclusions: The study concludes that the data presented does not support the view that academic attainment is a good predictor of personality traits. Implications for educational research, theory, and practice are considered.